Review of marketing research special issue : marketing legends - Naresh K. Malhotra (Bingley, U.K. : Emerald, 2011)
This volume will feature the work of Marketing Legends that have been announced so far. Each Legend will describe his contributions to the marketing discipline: Richard Bagozzi; Shelby Hunt; Philip Kotler; V. Kumar; Naresh K. Malhotra; Kent Monroe; Jagdish Sheth; Jerry Wind; Gerald Zaltman.
Reflections on a scholarly career : from inside out and back again / Richard P. Bagozzi -- Legends in marketing : a review of Shelby D. Hunt's volumes / Shelby D. Hunt, Shannon B. Rinaldo -- Philip Kotler's contributions to marketing theory and practice / Philip Kotler -- Looking through the marketing lens : my journey so far ... / V. Kumar -- Personal reflections on my research contributions to marketing / Naresh K. Malhotra -- Some personal reflections on pricing research / Kent B. Monroe -- A journey of an accidental marketing scholar / Balaji C. Krishnan, Jagdish N. Sheth -- Yoram'Jerry' Wind's contributions to marketing / Yoram'Jerry' Wind -- Lessons learned during a career / Gerald Zaltman.
Mode of access: World Wide Web.
Keywords: Marketing research